Selection of a field testing method for karst rock mass deformability by multi criteria decision analysis - Marčić, Danijela; Cerić, Anita; Kovačević, Meho Saša (Journal of Civil Engineering and Management, 2013)
The rock mass deformation modulus is an essential parameter for any numerical analysis and prediction of deformation in geotechnical engineering. Experience acquired using a large number of geotechnical projects in Croatia and the world indicates a somewhat unreliable determination of rock mass deformability based on correlation of classification results. The method of field testing for deformability can provide a more reliable insight into rock mass behaviour under loading conditions. The paper presents the most frequently used methods for field testing rock deformability. The benefits and disadvantages are shown of each particular method used in determining criteria and forming a ranking list of test methods using the multi criteria decision analysis. This ranking list of terrain testing for the rock mass stiffness is acquired on the basis of set criteria, assumes guidelines for compiling an exploratory works plan necessary for designing complex geotechnical structures in karst. Appropriate analyses of the sensitivity to changes in the significance of particular criteria was carried out including its effect on selecting the field method for testing karst rock mass deformability.